Effects of motivational interviews on childbirth perceptions and childbirthself-efficacy in nulliparous pregnant women: a randomised-controlled trial - Barut, Sumeyye; Ucar, Tuba (Routledge Journals, Taylor & Francis Ltd, 2023)
Background Motivational interviews (MI) may change the perspective of birth in pregnant women by changing their negative thoughts and increasing their self-efficacy. Objective This study was conducted to identify the effects of MI on childbirth perceptions and childbirth self-efficacy in nulliparous pregnant women who had traumatic childbirth perceptions. Methodology The research was carried out as a randomised-controlled trial with 166 pregnant women, including 83 experimental group and 83 control group. In the collection of data, the Traumatic Childbirth Perception Scale (TCPS) and the Childbirth Self-Efficacy Inventory (CSEI-C32) were utilised. Four sessions of MI were held with the pregnant women in the experimental group at weekly intervals whereas no initiative was applied to the pregnant women in the control group. Results As per the measurements performed after the MI held with the experimental group, it was found that the experimental group had a significantly lower mean TCPS score than the control group (p < 0.001). The experimental group also had a significantly higher mean CSEI-C32 score than the control group (p < 0.001). Conclusion MI can be effective in reducing the traumatic childbirth perceptions and increasing childbirth self-efficacy. However, further research is required to assess the effectiveness MI on traumatic birth perception and self-efficacy.
Keywords: Pregnancy; motivational interviewing; self-efficacy; perception; childbirth